Stigma as Social Stereotyping in the Area of Mental Health - Medynska, Yu. (Psychological Prospects Journal, 2013)
The concept of stigmatization of persons with mental disorders has been considered in the article. It was determined that for Ukrainian society inherent the type of stigmatization of persons with mental disorders, determined by the borderline defence mechanisms – projective identification, which correlates with the general borderline level of maturity of society.